PENGEMBANGAN VIDEO PEMBELAJARAN SISTEM KOORDINAT DIMENSI TIGA PADA MATA KULIAH GEOMETRI ANALITIK RUANG [DEVELOPMENT OF A THREE-DIMENSIONAL COORDINATE SYSTEM LEARNING VIDEO FOR A SPATIAL ANALYTICAL GEOMETRY COURSE] - Silitonga, R. H. Yanti; Molle, Juliana Selvina (Universitas Pelita Harapan, 2022)
Most students find it difficult to visualize in a three-dimensional coordinate system in a spatial analytic geometry course, so they need learning videos that can help them. The purpose of this study was to determine the results of an expert team's validation of a learning video about the three-dimensional coordinate system for a spatial analytic geometry course. In addition, this study also aimed to see the students' responses to the three-dimensional coordinate system learning video for the spatial analytic geometry course. This research used the ADDIE development research method (Analyze, Design, Develop, Implement, Evaluate). This research was conducted in the Mathematics Education Study Program at Pattimura University. The validation results of a team of 3 experts had an average score was 3.74. Based on the validation criteria, the expert team is in the very valid category. Furthermore, the total score obtained from the student response questionnaires is 1304 which is in the good category. The recommendation from this research is that further research needs to be done to see whether the use of this learning video can improve students' mathematical problem solving abilities in a three-dimensional coordinate system.BAHASA INDONESIA ABSTRACT: Sebagian besar mahasiswa kesulitan melakukan visualisasi dalam sistem koordinat dimensi tiga pada mata kuliah geometri analitik ruang sehingga membutuhkan video pembelajaran yang dapat membantu mahasiswa dalam melakukan visualisasi. Tujuan dari penelitian ini untuk mengetahui hasil validasi tim ahli terhadap video pembelajaran sistem koordinat dimensi tiga pada mata kuliah geometri analitik ruang. Selain itu, penelitian ini juga bertujuan untuk melihat respon mahasiswa terhadap video pembelajaran sistem koordinat dimensi tiga pada mata kuliah geometri analitik ruang. Penelitian ini menggunakan metode penelitian pengembangan dengan model pengembangan ADDIE (Analyze, Design, Develop, Implement, Evaluate). Penelitian ini dilaksanakan di Prodi Pendidikan Matematika Universitas Pattimura. Hasil validasi tim ahli yang berjumlah 3 orang diperoleh jumlah skor rata-rata mencapai 3,74. Berdasarkan kriteria kevalidan validasi tim ahli termasuk kategori sangat valid. Selanjutnya, diperoleh jumlah skor total hasil dari angket respon mahasiswa adalah 1304 berada pada kategori baik. Rekomendasi dari penelitian ini adalah perlu dilakukan penelitian lanjutan untuk melihat apakah penggunaan video pembelajaran ini dapat meningkatkan kemampuan pemecahan masalah matematis mahasiswa pada sistem koordinat dimensi tiga.